Study protocol: a clinical trial for improving mental health screening for Aboriginal and Torres Strait Islander pregnant women and mothers of young children using the Kimberley Mum's Mood Scale - Emma Carlin; Sarah J. Blondell; Yvonne Cadet-James; Sandra Campbell; Melissa Williams; Catherine Engelke; Des Taverner; Rhonda Marriott; Karen Edmonds; David Atkinson; Julia V. Marley (BMC, 2019)
Abstract Background Improving the rates of, and instruments used in, screening for perinatal depression and anxiety among Aboriginal and Torres Strait Islander women are important public health priorities. The Kimberley Mum's Mood Scale (KMMS) was developed and later validated as an effective and acceptable perinatal depression and anxiety screening tool for the Kimberley region under research conditions. Other regions have expressed interest in using the KMMS with perinatal Aboriginal and Torres Strait Islander women. It is, however, important to re-evaluate the KMMS in a larger Kimberley sample via a real world implementation study, and to test for applicability in other remote and regional environments before recommendations for wider use can be made. This paper outlines the protocol for evaluating the process of implementation and establishing the 'real world' validity and acceptability of the KMMS in the Kimberley, Pilbara and Far North Queensland in northern Australia. Methods The study will use a range of quantitative and qualitative methods across all sites. KMMS validation/revalidation internal consistency of Part 1 will be determined using Cronbach's alpha. Equivalence for identifying risk of depression and anxiety compared to a standard reference assessment will be determined from receiver operating characteristic curves. Sensitivity and specificity will be determined based on these cut-points. Qualitative methods of phenomenology will be used to explore concepts of KMMS user acceptability (women and health professionals). Additional process evaluation methods will collate, assess and report on KMMS quality review data, consultations with health service administrators and management, field notes, and other documentation from the research team. This information will be reported on using the Dynamic Sustainability Framework. Discussion This project is contributing to the important public health priority of screening Aboriginal and Torres Strait Islander women for perinatal depression and anxiety with tools that are meaningful and responsive to cultural and clinical needs. Identifying and addressing barriers to implementation contributes to our understanding of the complexity of improving routine clinical practie. Trial registration The study was registered retrospectively on 15/05/2019 with the Australian and New Zealand Clinical Trial registry (ACTRN12619000580178).